2002
DOI: 10.1111/j.1574-6968.2002.tb11165.x
|View full text |Cite
|
Sign up to set email alerts
|

amyP, a reporter gene to study strain degeneration inClostridium acetobutylicumATCC 824

Abstract: Clostridium acetobutylicum produces an extracellular alpha-amylase when grown on glucose as the sole carbon source. This enzyme was previously characterized from a biochemical point of view but its encoding gene was never identified. The 2283-bp amyP gene encodes a 83013-Da mature protein with an N-terminal domain that exhibits strong identity to the family 13 glycosyl hydrolases such as the Bacillus alpha-amylases. Transcriptional analysis revealed that amyP is transcribed in solventogenic but not in acidogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Considering that no potential CRE site can be found upstream of the amyA2 gene, and the fact that gene amyA2 showed no obvious change in transcriptional level when cells were cultivated with and without starch [37] and amyA2 -encoded α-amylase could be readily purified from the cells grown on d -glucose [52], this gene is unlikely subject to CcpA-dependent glucose repression in C. acetobutylicum . It should be noted here that amyA1 and amyA2 likely act as the major genes responsible for starch degradation in C. acetobutylicum , because the loss of the megaplasmid pSOL1 (harboring gene amyA1 and amyA2 ) caused serious defect in starch degradation [53]. …”
Section: Resultsmentioning
confidence: 99%
“…Considering that no potential CRE site can be found upstream of the amyA2 gene, and the fact that gene amyA2 showed no obvious change in transcriptional level when cells were cultivated with and without starch [37] and amyA2 -encoded α-amylase could be readily purified from the cells grown on d -glucose [52], this gene is unlikely subject to CcpA-dependent glucose repression in C. acetobutylicum . It should be noted here that amyA1 and amyA2 likely act as the major genes responsible for starch degradation in C. acetobutylicum , because the loss of the megaplasmid pSOL1 (harboring gene amyA1 and amyA2 ) caused serious defect in starch degradation [53]. …”
Section: Resultsmentioning
confidence: 99%
“…The DGS set was designed from the sequence of the amyP gene. The amyP gene, which encodes α-amylase, is located in pSOL1 and is transcribed during solventogenesis [4]. Table 1 shows the characteristics of the C. aceto set and the DGS set.…”
Section: Resultsmentioning
confidence: 99%
“…Cornillot et al reported that the degeneration of C. acetobutylicum ATCC 824, the most well-known butanol-producing bacteria, is related to the loss of the pSOL1 plasmid [8]. Because the pSOL1 plasmid has all of the genes (including ctfA, ctfB, adc, and aad) that are related to solvent formation, its loss leads to the degeneration of C. acetobutylicum ATCC 824 and the loss of its solvent production capabilities [4,5,8]. Therefore, the detection and quantification of the pSOL1 plasmid should be one of the approaches for monitoring degenerated C. acetobutylicum.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations